2008
DOI: 10.1007/s10620-008-0441-5
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between the Survivin C-31G Polymorphism and Gastric Cancer Risk in a Chinese Population

Abstract: Our results demonstrate that the survivin C-31G polymorphism may be involved in distal gastric carcinogenesis and tumor differentiation in a Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 34 publications
4
41
0
Order By: Relevance
“…Similar to other malignancies, the mechanism of gastric carcinogenesis involves a complex multi-stage and multi-factorial process that depends on gene-environment interactions (4). In previous epidemiological studies, genetic factors were demonstrated to play an important role in the development of gastric cancer (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other malignancies, the mechanism of gastric carcinogenesis involves a complex multi-stage and multi-factorial process that depends on gene-environment interactions (4). In previous epidemiological studies, genetic factors were demonstrated to play an important role in the development of gastric cancer (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Clarification of the survivin signaling pathway will provide new predictive and prognostic information for cancer diagnosis and could lead to the development of new therapeutic alternatives for a variety of cancers (Altieri, 2001;Yamamoto and Tanigawa, 2001). High survivin expression has been detected in several cancer types in humans, including colorectal cancer, hepatocellular cancer, lung cancer, pancreatic cancer, and osteosarcoma (Wang et al, 2009;Yang et al, 2009;Theodoropoulos et al, 2010;Upadhyay et al, 2011; Borges et al, 2011;Srivastava et al, 2012). Survivin is also expressed in breast cancer (Yamashita et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2009) reported that the C allele increased the risk of developing esophageal squamous cell carcinoma, and Wang et al (2009) reported that the risk of developing urothelial carcinoma was significantly greater in individuals with the GC + CC genotype than in individuals with the GG genotype. Consistent with the studies by Yang et al (2009) and Wang et al (2009), we found that the risk of developing breast cancer was significantly greater (by 1.413 times; 95% CI: 1.040-1.918) in individuals with the GC or CC genotype than in individuals with the GG genotype. Bayram et al (2011) studied the association between the -31G > C polymorphism and hepatocellular carcinoma in a Turkish population, but found no difference in the genotype distributions of patients with hepatocellular carcinoma and cancer-free individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Following this finding, researchers used in vitro promoter assays to demonstrate that the À31G allele had significantly lower transcriptional activity than the À31C allele, suggesting that the À31G/C polymorphism influences survivin expression, thus contributing to the genetic susceptibility to lung cancer. 13 Recently, many studies have investigated the role of the survivin À31G4C polymorphism in the etiology of various type of cancers, [13][14][15][16][17][18][19][20][21][22][23][24][25] including lung, gastric, bladder, esophageal, colorectal, urothelial, and pancreatic cancer. However, the results of these studies remain inconclusive.…”
Section: Introductionmentioning
confidence: 99%